Molecular characterization of genes encoding the quinolone resistance determining regions of Malaysian Streptococcus pneumoniae strains. - Kumari, N.; Subramaniam, G.; Navaratnam, P.; Sekaran, S. D. (Medknow Publications, 2008)
Genes encoding the quinolones resistance determining regions (QRDRs) in Streptococcus pneumoniae were detected by PCR and the sequence analysis was carried out to identify point mutations within these regions. The study was carried out to observe mutation patterns among S. pneumoniae strains in Malaysia. Antimicrobial susceptibility testing of 100 isolates was determined against various antibiotics, out of which 56 strains were categorised to have reduced susceptibility to ciprofloxacin (>or=2 microg/mL). These strains were subjected to PCR amplification for presence of the gyrA, parC , gyrB and parE genes. Eight representative strains with various susceptibilities to fluoroquinolones were sequenced. Two out of the eight isolates that were sequenced were shown to have a point mutation in the gyrA gene at position Ser81. The detection of mutation at codon Ser81 of the gyrA gene suggested the potential of developing fluoroquinolone resistance among S. pneumoniae isolates in Malaysia. However, further experimental work is required to confirm the involvement of this mutation in the development of fluoroquinolone resistance in Malaysia.